Berinteraksi dengan Buku - Ali, Muhammad (STAIN Ponorogo, 2010)
A book is not only a collection of papers that is written in word, but it is the message of life that could affect anyone who interacted with it, in accordance with the writer motivation and the reader condition. Ths article tries to study briefly how condition of the reader interacts with the book in the scope of humanity. yhe discussions through literature investigation and the writer experience personally are found in this article with many examples to make any closer to the topic that is discussed in the article.